2017
DOI: 10.18632/oncotarget.14831
|View full text |Cite
|
Sign up to set email alerts
|

Investigated the safety of intra-renal arterial transfusion of autologous CD34+ cells and time courses of creatinine levels, endothelial dysfunction biomarkers and micro-RNAs in chronic kidney disease patients-phase I clinical trial

Abstract: This was a phase I clinical trial to investigate the safety of autologous peripheral-blood-derived CD34+ cell therapy for patients with chronic kidney disease (CKD-treatment) (i.e., at Stages III and IV). Between November 2014 and October 2015, a total of 10 study patients were prospectively enrolled into this phase I trial. Patients who failed to enroll into the trial in the initial state of eligibility assessment were served as CKD-control group (n = 9). The health-control group was composed of 10 volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
8
32
0
Order By: Relevance
“…The most important finding in the present study was that, as compared with CKD only, intravenous administration of iPS‐MSCs significantly preserved residual renal function (ie reduced the levels of creatinine/BUN and the ratio of urine creatinine to urine protein) and reduced the kidney injury score (ie HE, stain pathological findings). Our findings corroborate those of previous studies . Additionally, the cellular expressions of podocyte components (ie ZO‐1, synaptopodin) and endothelial cell surface marker (ie CD31 + ) were preserved, whereas renal tubular injury biomarker (ie KIM‐1) was substantially reduced in CKD animals treated by iPS‐MSCs than in CKD only animals.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The most important finding in the present study was that, as compared with CKD only, intravenous administration of iPS‐MSCs significantly preserved residual renal function (ie reduced the levels of creatinine/BUN and the ratio of urine creatinine to urine protein) and reduced the kidney injury score (ie HE, stain pathological findings). Our findings corroborate those of previous studies . Additionally, the cellular expressions of podocyte components (ie ZO‐1, synaptopodin) and endothelial cell surface marker (ie CD31 + ) were preserved, whereas renal tubular injury biomarker (ie KIM‐1) was substantially reduced in CKD animals treated by iPS‐MSCs than in CKD only animals.…”
Section: Discussionsupporting
confidence: 91%
“…The fate and final destination of intravenous administration of stem cells for treatment of chronic phase of ischaemic‐related organ dysfunction, including in the setting of CKD, have not been fully investigated. This raises questions why some investigators in clinical trials tend towards intra‐arterial administration of stem cells into ischaemic organs for improving ischaemia‐related organ dysfunction, even though intra‐arterial administration of stem cells is more invasive than intravenous administration . The novel finding in the present study was that, using MRI examination, we precisely identified that intravenously administered iPS‐MSC SPIONs (ie iron‐labelled iPS‐MSCs) settled in kidney parenchyma of CKD, but not in healthy, kidney, highlighting that a chronically dysfunctional organ can capture stem cells for tissue/organ repair and regeneration.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations